Impact of Online Freelancing on Economic Growth of Developing Countries Like Pakistan - Muhammad Naveed Ahsan; Muhammad Rafiq; Moeez Hassan; Nagina Gohar (Cita Konsultindo Research Center, 2022)
In the digital age, freelancing has had a huge impact and as an alternate job option, has grown more popular. In this field, studies have been scarce. The link between freelancing and economic growth is investigated in this study. A total of 100 freelancers were interviewed using a Google form. The current administration has set aside and given special attention to assisting freelancers, with the goal of allowing them to play an important role in their families as a whole. Anyone with particular skills can work as a freelancer without getting a graduate degree. However, in Pakistan, a freelancer's life is already difficult due to poor working conditions, a lack of affordable internet, and the exorbitant cost of technical peripherals. Furthermore, the social components are more difficult because many people here are discouraged from seeking demanding work rather than a government job. Hence, because of developing countries, online freelancing can create employment.